Nutrification of Moringa Leaf Flour (Moringa oleifera) in Wet Noodle Production and Its Effect on Macronutrient Content - Abdul Hakim Laenggeng; Lilies Tangge; Rafiqa Rafiqa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
In this study, we analyzed the effects of different concentrations of Moringa oleifera leaf flour on the carbohydrate, protein, and fat content of wet noodles. We conducted an experimental study using a Completely Randomized Design (CRD) and analyzed the data through ANOVA and LSD tests using SPSS 21 software. The results showed that fortifying wet noodles with Moringa leaf flour significantly altered their macronutrient composition. The carbohydrate content decreased from 28.286% in treatment 2 to 27.350% in treatment 3 and 25.677% in treatment 4. In contrast, the protein content increased from 5.289% in treatment 2 to 5.905% in treatment 3 and 6.345% in treatment 4. Similarly, the fat content rose from 0.439% in treatment 2 to 0.554% in treatment 3 and 0.645% in treatment 4. These findings suggest that increasing concentrations of Moringa leaf flour can improve the nutritional profile of wet noodles, particularly by enhancing their protein and fat content while reducing carbohydrate levels.